PENGARUH DISIPLIN DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI BADAN PENGUSAHAAN (BP) BATAM - Timbul Dompak; Dedi Epriadi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
This study aims to investigate the effects of discipline and leadership on the performance employees of Badan Pengusahaan (BP) Batam. By giving respondents questionnaires, this study uses quantitative methods. 100 people make up the research sample. The research yielded the following conclusions: (1) There is a partial influence of discipline on employee performance, as shown by a t-count value of (7.351) > t-table (1.984), (2) There is a partial influence of leadership on employee performance, as shown by a t-count value of (3.632) > t-table (1.984), and (3) There is a simultaneous influence of discipline and leadership on employee performance, as shown by an F-count (126.347) > F-table (3.09).